Memantine ER Maintains Patient Response in Moderate to Severe Alzheimer's Disease: Post Hoc Analyses From a Randomized, Controlled, Clinical Trial of Patients Treated With Cholinesterase Inhibitors. Issue 3 (July 2018) - Grossberg, George T.; Alva, Gustavo; Hendrix, Suzanne; Ellison, Noel; Kane, Mary C.; Edwards, John
Abstract : Memantine extended release (ER) significantly outperformed placebo on co-primary endpoints of Clinician's Interview-based Impression of Change Plus Caregiver Input (CIBIC-Plus) and baseline to endpoint changes on the Severe Impairment Battery (SIB) in a 24-week, randomized trial (NCT00322153) in patients with moderate to severe Alzheimer's disease taking a cholinesterase inhibitor (ChEI). A post hoc analysis compared patients receiving memantine ER/ChEI to placebo/ChEI for time to onset of response and if the response was maintained (achieving improvement at weeks 8, 12, or 18 and maintaining through endpoint/week 24) on the SIB, the Neuropsychiatric Inventory (NPI), CIBIC-Plus, and Activities of Daily Living (ADL) using Fisher exact test. A second post hoc analysis compared percentages of patients for all possible combinations of 2 to 4 assessments with either no decline or clinically notable response using Wald χ 2 . Significantly greater percentages of memantine ER/ChEI patients achieved an early response that was maintained on SIB, NPI, and CIBIC-Plus ( P <0.05) versus placebo/ChEI. Significantly greater percentages of memantine ER/ChEI-treated patients achieved and maintained a clinically notable response on ADL/NPI, SIB/ADL/NPI, and SIB/ADL/CIBIC-Plus, compared with placebo/ChEI ( P <0.05). Memantine ER results in early, maintained improvement in patients with moderate to severe Alzheimer's disease concurrently taking ChEIs, compared with cholinesterase treatment alone. Abstract : Supplemental Digital Content is available in the text.